2008
DOI: 10.1080/09575140802393793
|View full text |Cite
|
Sign up to set email alerts
|

Teacher‐involved conversations with young children during small group activity

Abstract: , "Teacher-involved conversations with young children during small group activity" (2008 AbstractThis qualitative study examines the conversations of two preschool teachers with two-and three-year-old children during small-group activity settings in two highquality child development centers. Using interviews, observations and videotaping of small-group activities, the conversations are characterized in terms of the kind and function of language, the usage of cognitive demands and the reciprocal nature of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 14 publications
0
28
0
2
Order By: Relevance
“…Teachers' dominating position in conversations in day care is documented earlier (see e.g. Cote, 2001;Durden & Dangel, 2008;Girolametto, Weitzman, Lieshout, & Duff, 2000;Wood, McMahon, & Cranstoun, 1980). The fact that the children in the example presented above, at two years of age, are able to continue the conversations when the teacher leaves the table for some time or she holds herself back for a while (attentive distance), indicates the promising opportunities embedded in toddlers' peer talk.…”
Section: Conversationsmentioning
confidence: 91%
“…Teachers' dominating position in conversations in day care is documented earlier (see e.g. Cote, 2001;Durden & Dangel, 2008;Girolametto, Weitzman, Lieshout, & Duff, 2000;Wood, McMahon, & Cranstoun, 1980). The fact that the children in the example presented above, at two years of age, are able to continue the conversations when the teacher leaves the table for some time or she holds herself back for a while (attentive distance), indicates the promising opportunities embedded in toddlers' peer talk.…”
Section: Conversationsmentioning
confidence: 91%
“…Linked to this, training in elaborative style and reminiscing could form part of early childhood educator induction and CPD. Many studies into teacher talk in early childhood settings have found the majority of talk to be simple and cognitively undemanding for children (Dickinson et al 2008;Durden and Dangel 2008;Girolametto and Weitzman 2002;Chen and de Groot Kim 2014), demonstrating that there is a need for training to improve the quality of early childhood educator dialog. And there is evidence that such training is possible from parent intervention studies (cited above) and studies such as that by Cain (2004), where researchers were trained to use different elaborative styles with the target and control group.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…The children need all the opportunities to give them a chance to answer, to respond, or to question back. According to Durden and Dangel (2008), the qualities of interaction are characterized by the teacher listening to, repeating the child's talk, modelling complete thoughts and compliments children on their efforts.…”
Section: Responsesmentioning
confidence: 99%